KONFLIK SOSIAL ANTARA WARGA DAN PETUGAS PENGELOLA TPA SAMPAH DI KECAMATAN PONTIANAK UTARA - Ramadaniarsih, Devi Sari; Imran, Imran; Alhidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The goal of this study is to know the social conflict that occurs between citizen and the officers of waste management landfills (TPA) on Jl. Kebangkitan Sosial, North Pontianak. Furthermore, this study use a qualitative approach with descriptive methodology. The data collection techniques are observation, interviews, and documentation. The data are analysed and presented in the form of descriptive qualitative data. There are 4 informants, consisting of two citizen from different neighbourhood (RT) and two officers from the waste landfill management institution. The results of this study indicate that 1) the cause of this conflict is the rapid social change in the community, additionally the less effective in controlling leachate caused the waste to overflow and pollute the citizens' water sources during the rainy season; 2) the impact of the conflict is the management of waste landfill began to improve their work system and fix the special canal that accommodate leachate waste; and 3) the efforts to overcome conflicts that occur between the citizen and the officers of waste management institutions on Jl. Kebangkitan Nasional is using mediation, where the problems are discussed and try to find the solutions together. Key words: Social conflik, Waste, Contamination